Treatment Outcomes and Quality of Life in Oropharyngeal Cancer after Surgery-based versus Radiation-based Treatment - Kim, Tae Wook (Korean Society of Otorhinolaryngology-Head and Neck Surgery, 2010)
OBJECTIVES: Advances in reconstruction and conservative surgery and the importance of quality of life (QOL) encouraged this reevaluation of surgery-based treatments for oropharyngeal cancer. We tried to compare treatment outcome and QOL after surgery-based versus radiation-based treatment in oropharyngeal cancer. METHODS: The 133 eligible patients were divided into surgery-based and radiotherapy (RT)-based treatment groups. Medical records were reviewed, and EORTC QLQ-C30 and HN65 questionnaires were completed for survivors. Three-year overall survivals, disease-free survivals, locoregional control rates, and QOL scores were compared between the two groups. RESULTS: Demographic data and overall stages were not significantly different between the two groups, and all survival rates were non-significantly different, either. The scores for most QOL items were equivalent, however, for a few items, scores were significantly better in surgery-based group. CONCLUSION: The surgery-based group achieved equivalent treatment outcomes and slightly better QOL scores than the RT-based group. The results of this study suggest that surgery could still be considered as a first-line therapy for oropharyngeal cancer.